Investigation of the Effect of nozzle temperature in fused deposition modelling on the mechanical properties and degradation behaviour of 3d-printed PLA/PCL/HA biocomposite filaments - Rifky, Ismail; Fitriyana, Deni Fajar; Arizsa Athallah, Muhammad Dzaky; Nugraha, Fariz Wisda; Priwintoko, Baharudin; Bayuseno, Athanasius Priharyoto; Anis, samsudin; Siregar, Januar Parlaungan; Cionita, Tezara; Novriadi, Dwi; Muslim, Opa Fajar (Semarak Ilmu Publishing, 2025)
The invention of three-dimensional (3D) printing has transformed the medical field, offering sophisticated and accurate options for surgery planning, education, and individualized therapy. Although 3D printing is widely used, little is known about how the parameters of the process affect the properties of composites reinforced with hydroxyapatite (HA) that has been derived from crab shells. The present study investigates the influence of nozzle temperature in fused deposition modeling (FDM) on the physical, mechanical and degrading properties of PLA/PCL/HA biocomposite specimens, assessing their viability as biodegradable implant materials. The biocomposites were produced with a mixture of polylactic acid (PLA), polycaprolactone (PCL), and hydroxyapatite (HA) sourced from crab shells. The nozzle temperature during the printing process was adjusted between 190°C and 215°C to assess its impact on key properties, including density, flexural strength, flexural modulus, and degradation rate. The results highlight the significance of nozzle temperature in affecting the performance of the biocomposites. The specimens produced at 205°C exhibited superior mechanical properties, featuring a flexural strength of 41.09 MPa, a flexural modulus of 474.789 MPa, and a density of 1.28 g/cm³, closely resembling the mechanical and density attributes of human cortical bone. Furthermore, this specimen demonstrated the lowest degradation rate, rendering it very appropriates for biomedical applications. This study utilizes crab shell waste to create biodegradable medical implants, enhancing healthcare while reducing environmental impact. Advanced 3D printing integrates sustainable practices, aligning with Sustainable Development Goals (SDGs) like Good Health (SDG 3), Innovation (SDG 9), and Marine Sustainability (SDG 14).